Single Active Element Based Voltage-Mode Multifunction Filter. (17th August 2014) - Mohan, Jitendra; Chaturvedi, Bhartendu; Maheshwari, Sudhanshu
Abstract : The paper presents a new voltage-mode multifunction filter. The proposed filter employs single modified fully differential second generation current conveyor (FDCCII), two grounded capacitors, and three resistors. The proposed circuit enjoys the employment of two grounded capacitors (attractive for absorbing shunt parasitic capacitance and ideal for IC implementation). The proposed circuit provides all five generic filter responses (low pass (LP), high pass (HP), band pass (BP), notch (NH), and all pass (AP) filter responses) simultaneously with single input. The novel proposed filter has low active and passive sensitivities. A number of time domain and frequency domain simulation results depicted through PSPICE using 0.18  µ m TSMC process parameters are included to validate the theory. The proposed circuit is expected to enhance the existing knowledge on the subject.